The ACE advantage : how smart companies unleash talent for optimal performance - Schiemann, William (Human resource management online (text), 2012)
Executives are beginning to realize that the most effective way to fight the recession or to conquer competitive challenges is not to retreat, but to optimize every asset under management--especially an organization's human resources. This groundbreaking book argues against historical assumptions regarding managing talent and how human capital should be perceived. Introducing three factors--Alignment, Capabilities, and Engagement (ACE)--this guide demonstrates how ACE forms the framework for optimizing, managing, and measuring the value contribution of human resources to the strategic and operati.